Hubungan Keterlibatan Siswa dalam Permainan Atletik Lari Jarak Pendek dengan Keterampilan Sosial Siswa SMA dalam Pembelajaran PJOK - M. Yusuf Faiqul Mu'ammar; Topo Yono; Bahtiar Hari Hardovi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to analyze the relationship between student involvement in short-distance athletics and the social skills of high school students in Physical Education (PJOK) learning. The research method used a quantitative approach with a correlational approach. The study population involved 42 students from Arjasa State High School in Jember, selected using a purposive sampling technique. The research instrument was a student involvement and social skills questionnaire, which had been tested for validity and reliability. Data were analyzed using the Pearson Product Moment correlation test with SPSS. The results showed a very strong positive relationship between student involvement in short-distance athletics and social skills, with a correlation coefficient of r = 0.794 and a significance level of p = 0.000. The conclusion of this study confirms that the higher the student involvement in short-distance athletics, the better their social skills. Therefore, game-based PJOK learning can be an effective strategy for developing students' social aspects in addition to physical abilities. In conclusion, this study proves that student involvement in short-distance running athletics games has a positive and very strong relationship with students' social skills in PJOK learning. Keywords: student involvement, short-distance athletics, social skills, PJOK